2008
DOI: 10.1529/biophysj.108.135152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protein Dynamics in Asymmetric Cell Division by Scanning Fluorescence Correlation Spectroscopy

Abstract: The development and differentiation of complex organisms from the single fertilized egg is regulated by a variety of processes that all rely on the distribution and interaction of proteins. Despite the tight regulation of these processes with respect to temporal and spatial protein localization, exact quantification of the underlying parameters, such as concentrations and distribution coefficients, has so far been problematic. Recent experiments suggest that fluorescence correlation spectroscopy on a single mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…In plant cells, the mobility of Nod factors of Rhizobium bacteria was studied upon binding to the cell wall of Vicia sativa root hairs [48]. FCS has also been applied to several other model organisms, such as the embryos of zebrafish [49], medaka [50], nematodes [51] and fruit flies [52].…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In plant cells, the mobility of Nod factors of Rhizobium bacteria was studied upon binding to the cell wall of Vicia sativa root hairs [48]. FCS has also been applied to several other model organisms, such as the embryos of zebrafish [49], medaka [50], nematodes [51] and fruit flies [52].…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…Larson et al examined the mobility and multimerization of the polyprotein Gag, a key player in the assembly of retroviruses in the cytosol of live cells, and found that Gag is part of a large complex in the cytoplasm [33]. Going one step further, it was recently shown that two-photon FCS in combination with beam-scanning can be used to characterize protein dynamics in the cortex of a developing Caenorhabditis elegans embryo [51]. The developing embryo is an especially challenging system, since its movement makes it difficult to separate the slow motion of the proteins of interest from the motion of the whole organism.…”
Section: Two-photon Excitationmentioning
confidence: 99%
“…From the hardware side the current trends are (i) dual spot measurement to measure FCS simultaneously at various locations (9) and/or to access to absolute diffusion coefficient (8), (ii) multispot FCS using EMCCD cameras as detector (10). From the data analysis side, recent development focus on the improvement of spatio-temporal information by means of scanning FCS (11) and Image correlation spectroscopy techniques (12) that give access to both temporal and spatial correlations. Another powerful variant of FCS is Fluorescence Cross Correlation Spectroscopy (FCCS), which extends the capabilities of standard FCS by introducing two different fluorescent probes with distinct excitation and/or emission properties, which can be detected in the same confocal volume.…”
Section: Fcs Data Analysismentioning
confidence: 99%
“…13 Without modifying the scanning features, the dual spot scheme that we propose allows to address correlation delays that are significantly shorter. Therefore we believe that this approach can provide more accurate measurements.…”
Section: Dual Spot Scanning Fcsmentioning
confidence: 99%